Insights from Scientific Drilling on Rifted Continental Margins - Louden, Keith; Lau, Helen (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2001)
Summary Sampling of sedimentary and crustal formations across rifted continental margins has long been a priority of DSDP,ODP, and other scientific ocean drilling. Recent results of drilling and related geophysical surveys across several margin segments in the North Atlantic have revealed that continents break apart in two fundamentally different ways. Volcanic margins form when rapid mantle up-welling produces a large amount of melt just prior to and during rifting. On non-volcanic margins, slow rates of rifting the continental crust expose regions of serpentinized mantle with little evidence of melting. Sampling, however, has thus far been restricted to regions of thin sediment cover, which has limited ourability to study the full range of rifted margin evolurion. The next phase of scientific drilling will have enhanced capabilities that will allow drilling of both shallow- and deep-water basins, including those with thick sediments with hydrocar-bon potential, such as the outer GrandBanks and Scotian margins. To make this a reality, it will be essential to combine both industry and academic interests and work to ensure continued Canadian participation.